2022
DOI: 10.6018/eglobal.474821
|View full text |Cite
|
Sign up to set email alerts
|

Diferentes actitudes hacia la sexualidad entre estudiantes de Enfermería de primero y cuarto curso

Abstract: Objective: To evaluate whether attitudes towards sexuality acquired by students during a Spanish nursing degree are sufficient for their performance in professional practice. Methods: This is a descriptive, cross-sectional, and quantitative study based on a self-completion survey composed of standardized scales that compare sexual attitudes among 101 first-year students with 86 fourth-year students. The 187 nursing students, 24 men and 163 women were between 18 and 60 years old (Mage=21.21, SD=5.48). The evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
3
1
1
Order By: Relevance
“…When evaluating double standards towards sexuality, a mean score on the DSS of 30.35 was observed. Alonso‐Martínez et al ( 2022 ) found lower scores reaching a difference of almost half of ours (17.53), meaning they had lower adherence to the greater degree of sexual freedom for men than for women. Other authors, however, find average scores higher than ours by 10 points in the case of university men and more than 13 points in university women (Sierra et al, 2007 ).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…When evaluating double standards towards sexuality, a mean score on the DSS of 30.35 was observed. Alonso‐Martínez et al ( 2022 ) found lower scores reaching a difference of almost half of ours (17.53), meaning they had lower adherence to the greater degree of sexual freedom for men than for women. Other authors, however, find average scores higher than ours by 10 points in the case of university men and more than 13 points in university women (Sierra et al, 2007 ).…”
Section: Discussioncontrasting
confidence: 56%
“…The mean score on the ATSS was 109.60. Alonso‐Martínez et al ( 2022 ) found a mean score five points higher in their sample of 187 undergraduate nursing students. Although these authors differentiate by year (first year and fourth year), similarities are still present in the scores of both groups.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the USA, it has reached about 200 new cases annually, affecting both sexes equally [66]. This syndrome is associated with a high mortality rate, and most deaths occur within hospital settings despite efforts by healthcare teams to make accurate diagnoses [67].…”
Section: Discussionmentioning
confidence: 99%
“…Sus resultados, en la línea de lo expuesto, revelaron que los y las estudiantes tenían unas actitudes más liberales hacia comportamientos relacionados con la heterosexualidad, el sexo comercial y la pornografía y el autoerotismo; y actitudes más conservadoras o erotofóbicas hacia comportamientos relacionados con la variabilidad y diversidad sexual y la homosexualidad (4,15) . Respecto a la formación en sexología durante los estudios de Enfermería y pese a que se supone necesario que los y las profesionales de enfermería integren la sexualidad humana en su formación para poder brindar una atención de calidad a sus pacientes, a los que deben saber entender de manera holística; ésta suele brillar por su ausencia o, en la gran mayoría de ocasiones, disfrazarse para tratar únicamente aquello relativo a la anatomía genital, la reproducción, el embarazo y el parto; además de ser abordada desde un enfoque de neutralidad, prohibiciones y asexualización (4,(16)(17)(18) .…”
Section: Introductionunclassified